(untitled) (International Journal of Food and Nutritional Sciences, 2022)
the evolving landscape of transportation systems, focusing on the design and operation of efficient, sustainable, and intelligent frameworks. The integration of connected and automated vehicles (CAVs) and alternative fuel vehicles (AFVs) plays a pivotal role in achieving these objectives. The paper reviews current advancements, challenges, and opportunities in the field, emphasizing the synergy between these technologies to enhance overall system performance. Key aspects include the impact of CAVs on traffic management, safety, and energy efficiency, as well as the role of AFVs in reducing environmental footprints. The paper also examines the integration of intelligent transportation systems (ITS) for seamless communication and data exchange. Through a comprehensive review of existing literature, case studies, and emerging technologies, this research paper aims to provide insights into the transformative potential of connected and automated vehicles and alternative fuel technologies in reshaping the future of transportation systems.